Evaluasi Pencegahan dan Penanggulangan COVID-19 Pada Industri Petrokimia di Sumatera Selatan - Arinda, Sri; Modjo, Robiana (E-Jurnal Medika Udayana; Vol 11 No 5 (2022): E-Jurnal Medika Udayana, 2022)
The COVID-19 pandemic has a global impact, not only on health but also on the economic sector. In order to support the sustainability of the economy, various industries continue to carry out business activities during the COVID-19 pandemic. To support this situation, various parties, both government and international institutions such as the International Labour Organization (ILO) have developed guidelines for preventing and controlling COVID-19 in the workplace. Further evaluation of the implementation of these guidelines is very important to determine the company's level of readiness in dealing with the COVID-19 pandemic. This study was conducted at PT X, one of the Petrochemical Companies in South Sumatra. This study was conducted in September 2021 – January 2022. This is a semi-quantitative study with a Cross Sectional design. Data were collected through direct observation and review of company documents based on Kepmenkes No. HK.01.07/Menkes/328/2020, SE Minister of Manpower No. M/7/AS.02.02/V/2020 and the 2020 ILO guidelines. Data triangulation was carried out by in-depth interviews with 7 key informants. The results showed that PT X has implemented the COVID-19 prevention and control programs with a readiness level of 91.3%. However, there are programs that have not been implemented (the prevention of stigma and discrimination, evaluation of worker's knowledge and behavior, and also the structure of the COVID-19 team has not been included in the P2K3 structure. It is recommended to PT X to implement these programs in order to optimize the efforts that have been made. Keywords: COVID-19, Workplace, Prevention and Control